Home-Made Membraneless Vaporization Gas-Liquid Separator for Colorimetric Determination of Ethanol in Alcoholic Beverages - Vanpaseuth Phouthavong; Hayato Inoue; Kesiny Phomkeona; Vanseng Chounlamany (Journal of Analytical Methods in Chemistry)
This work utilized the simplicity of a so-called membraneless vaporization (MBL-VP) unit as a gas separator for the colorimetric determination of ethanol in alcoholic beverages. A beverage sample with a volume of 1 mL was directly injected into a small container which was hung from a lid inside a closed 40 mL reused glass bottle without pretreatment such as distillation. An acidified potassium dichromate (Cr2O72−) acceptor solution, preadded to the glass bottle, was reduced to Chromium (III) ion by the diffusion of vaporized ethanol from the sample. After 5 min, the absorbing solution was collected for colorimetric detection at 590 nm. The unit manually quantifies ethanol in the range 1.0–90% (v/v) with satisfactory interday precision but without matrix effect (recovery 89−109%). The method was validated with the conventional distillation/pycnometer method which showed no significant difference of ethanol contents between those two methods and the declared values of 12 alcoholic beverages, indicating sufficient accuracy. Analyses of alcoholic beverages using this method were successful with benefits of simplicity, cheapness, and less energy consumption.